Business model of the sharing economy platform: Who are the 'winners' and who are the 'losers' of the COVID-19 pandemic? - Suzana Stefanović (Economic Themes, 2021)
The increasing digitalization of business activities in recent years has been a significant impetus to business model innovation. In this sense, we are witnessing the success of companies that base their businesses on the digital platform model. Therefore, the basic purpose of this paper is to stress out the very essence of platformization as a business model, which is based on the implementation of digital technologies, as well as to point out the characteristics - advantages and disadvantages of the so-called 'sharing economy' model. Also, the purpose and goal of the paper is to point out how the characteristics of different types of platforms, especially of sharing economy platforms, affect their business success, i.e. market value, but also vulnerability in case of adverse effects of external factors, such as the current corona virus pandemic. Using both the classical methodology of theoretical research, based on insights into an available literature on the topic, and the results of research of world best practice, as well as monitoring statistical indicators of market value of the world's best companies, the results confirm the initial assumption that nowdays companies which implement business model of the platform prevail. However, the results of the research also showed the vulnerability of the platforms, especially those based on the sharing economy, in the conditions of a corona virus pandemic. Given that there is very little research in the academic literature on the economic consequences of the current COVID-19 pandemic, the originality and significance of the research is in an attempt to stress out the consequences of the pandemic on the current market value and position of platform companies, and also on their survival and growth in the future.
Keywords: M13; M15; M21; O33; 330; business model; digitalization; platform; sharing economy; market capitalization; COVID-19